4-SUBSTITUTED-5,5-DIMETHYL OXAZOLIDIN-2-ONES AS EFFECTIVE CHIRAL AUXILIARIES FOR ENOLATE ALKYLATIONS AND MICHAEL ADDITIONS - Davies, S; Sanganee, H (1995)
4-(Methyl, phenyl, benzyl, and i-propyl)-5,5-dimethyl-oxazolidin-2-ones, readily available from α-amino acids, are shown to be effective chiral auxiliaries for stereoselective enolate alkylations and conjugate additions of attached N-acyl moieties. © 1995.